1990
DOI: 10.2134/jeq1990.00472425001900030031x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Management Practices for Reducing Pesticide Runoff from Sloping Cropland in Illinois

Abstract: The influence of tillage system and contouring practice on runoff of soil-applied alachlor ]2-chloro-2',6'-diethyl-N-(methoxymethyl) acetanilide], carbofuran (2,3-dihydro-2,2-dimethyl-7-benzofuranyl methylcarbamate), and terbufos (S-](tert-butylthio)methyl] O,O-diethyl phosphorodithioate) from small plots (30 2) w ere studied u sing a rainfall simulator. Plots were planted in corn (Zea mays L.) in 1983, soybean ]Glycine max (L.) Merr.] in 1984, and corn in 1985. Runoff was measured during a 60-min event with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
24
2

Year Published

1997
1997
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(28 citation statements)
references
References 0 publications
2
24
2
Order By: Relevance
“…The percent of total alachlor lost in the water phase was not different among tillage ( P = 0.970) or herbicide application method ( P = 0.600) and averaged 88% for both years. Other studies have shown similar percentages of total alachlor loss in the water phase (Felsot et al, 1990; Khakural et al, 1994). Although the concentration of alachlor was much greater per unit mass of sediment than per unit mass of water, the total mass of sediment lost in runoff was small compared with the mass of water.…”
Section: Resultssupporting
confidence: 58%
See 2 more Smart Citations
“…The percent of total alachlor lost in the water phase was not different among tillage ( P = 0.970) or herbicide application method ( P = 0.600) and averaged 88% for both years. Other studies have shown similar percentages of total alachlor loss in the water phase (Felsot et al, 1990; Khakural et al, 1994). Although the concentration of alachlor was much greater per unit mass of sediment than per unit mass of water, the total mass of sediment lost in runoff was small compared with the mass of water.…”
Section: Resultssupporting
confidence: 58%
“…These values are similar to those obtained in other runoff studies. For example, Felsot et al (1990) reported K d values for alachlor and eroded sediment ranging from 5.6 to 8.4 L kg −1 and Baker et al (1978) reported values for alachlor as high as 10.8 L kg −1 For cyanazine and eroded sediments, a K d value of 2.8 was reported (Hall et al, 1984).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies indicated that conservation tillage was inefficient in controlling runoff when heavy rainfall occurs quickly after pesticide application (Rector et al, 2003;Shipitalo and Owens, 2003;Shipitalo and Owens, 2006). Moreover, most pesticide loss by Felsot et al, 1990) Alachlor 3.36 --941, 1158, 824, 926, 1029, 860 5, 6, 7, 18, -, 1 1, 4, 7, 18, 18 -50, 35-38 31-56, 35-48 16-24, 34-47 2.2-9.4, 2.1-4.7 1.7-8.1, 1.9-2.5 0.5-1.6, 1.7-3.0 (Myers et al, 1995) Atrazine 0.9 0.9 Inc. (Malone et al, 1996) 392 L. Alletto et al (Kenimer et al, 1987) 1 Codes of tillage practices are reported in Table I. Loc: seed row localisation of the pesticide treatment.…”
Section: Runoffmentioning
confidence: 99%
“…Pesticide incorporation into soil through superficial tillage was found to significantly reduce losses by runoff (Franti et al, 1998;Olson et al, 1998;Rector et al, 2003) but this technique is not suitable for no-tillage systems and may lead to an increase in losses by leaching. Finally, whatever the tillage system, soil tillage along isotopographic lines rather than up-and-down slope was efficient in reducing transfers by runoff (Felsot et al, 1990).…”
mentioning
confidence: 92%